Improvement of structural stability for multi – storey building by using composite column and cable connection - Arvin, Yashar (2010)
Two methods for the improvement of structural stability of the building are introduced. These methods ensure that the structural building is safe, reliable and economy with the production of small deflection against seismic loading and any other external effect. The application of composite column as flexible material or non-rigid part of the frame structure is introduced and capable to absorb energy comes from the action and reaction of loading. The second approach in this research is by introducing active spring or prestressed cable connections in order to reduce the instability of structural building. The effect of P-delta on two methods stated is studied by performing non-linear analysis by using SAP2000 software on the building and compared the analysis results to conventional structural building with rigid connection. The results from SAP2000 shows that the proposed composite column and structural building with prestressed cable connection provide small deflections under loading compared with the deflection induced by conventional building with rigid connection. This finding proves that the proposed methods for building construction can increase the stability of the structural building.